Reevaluating vitamin C in sepsis and septic shock: a potential benefit in severe cases? - Alissa, Abdulrahman; Alrashed, Mohammed A.; Alshaya, Abdulrahman I.; Al Sulaiman, Khalid; Alharbi, Shmeylan (Frontiers in Medicine, 2024)
Vitamin C (Ascorbic acid) has evolved as an emergent co-intervention for sepsis and septic shock patients. Multiple studies discussed the pathophysiological value of vitamin C to reserve endothelial functionality and improve microcirculatory flow in these patients. Nevertheless, most randomized clinical trials failed to show the clinical impact of adding vitamin C to sepsis and septic shock. Pneumonia is the most common infection to induce sepsis and septic shock, which could be an acute respiratory distress syndrome. Preliminary in-vitro data support the role of vitamin C in mitigating the risk of acute respiratory distress syndrome (ARDS) development.This review aims to compare and contrast these trials and explore differences in their patients' populations, methodologies, and outcomes, emphasizing pneumonia-induced sepsis and septic shock.